The Bible in the Patristic period - Szram, Mariusz; Wysocki, Marcin (Studia Patristica, 2021)
This 103rd volume in the Studia Patristica series consists of 15 articles devoted to the translations and interpretations of the Bible in the Patristic period, and is the result of the Third International Patristic Conference, which was held at the John Paul II Catholic University of Lublin (Lublin, Poland) on October 16-17, 2019. The articles presented in this volume cover the entire patristic period and discuss various issues related to the meaning and interpretation of the Bible in the Aleandrian milieu and among Egyptian Monks, in the works of Origen, Jerome, Cyril, Philastrius of Brescia, Augustine, Paulinus of Nola, John Chrysostom and Sergius the Stylite. The articles presented allow us to better understand what the Bible meant to the authors of the Patristic period, and how they used it in their lives and works. --